2013
DOI: 10.1371/journal.pntd.0002252
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distribution, Age Pattern and Sites of Lesions in a Cohort of Buruli Ulcer Patients from the Mapé Basin of Cameroon

Abstract: Buruli ulcer (BU), a neglected tropical disease of the skin, caused by Mycobacterium ulcerans, occurs most frequently in children in West Africa. Risk factors for BU include proximity to slow flowing water, poor wound care and not wearing protective clothing. Man-made alterations of the environment have been suggested to lead to increased BU incidence. M. ulcerans DNA has been detected in the environment, water bugs and recently also in mosquitoes. Despite these findings, the mode of transmission of BU remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
100
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 49 publications
12
100
2
2
Order By: Relevance
“…Similarly, swimming with an exposed wound does not increase the risk of contracting BU infection. This finding is however contrary to the findings in Cameroon [4,23]. There was no evidence suggesting that the BU patients had wounds before contracting the disease.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…Similarly, swimming with an exposed wound does not increase the risk of contracting BU infection. This finding is however contrary to the findings in Cameroon [4,23]. There was no evidence suggesting that the BU patients had wounds before contracting the disease.…”
Section: Discussioncontrasting
confidence: 93%
“…This current result agrees with the findings of Bratschi et al in Cameroon where BU hotspots were identified around the Mbam River [4]. This study also found that the local BU endemic areas are larger than previously described by Chukwukezie et al [12] and Nwodo [9], though some the hotspots were not significant at 95%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…4,5 The disease usually manifests itself as a painless nodule, a firm plaque, or an edematous lesion, which soon ulcerates with characteristic undermined edges.…”
Section: Introductionmentioning
confidence: 99%